AVIATION SECURITY TECHNOLOGIES IN THE TIME OF THE COVID-19 - Аланія, Давид Лідерович; Тепнадзе, Серго Амбросович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The goal of this article is to identify objective preconditions for developing and applying new technologies in aviation security at the time of pandemic and during post-pandemic times. The article focuses on the necessity to ensure the needs through securing an appropriate legal and normative framework pertinent to this process. Research methods: applying systemic-structural and communication methods helped the researcher to identify and analyze the common trends in applying new technologies to ensure security of aviation and address the respective challenges of legal nature. Results: as a result of academic research, the main directions for securing a legal and normative framework allowing to apply news technologies in ensuring aviation security at the time of COVID-19 crisis and during post-crisis times, were formulated. Discussion: the COVID-19 crisis is a global threat that has considerably affected security of aviation. At the same time, this threat has served as an impetus for the adoption of measures for use of new technologies in security of aviation as well as an impetus for ensuring respective legal and normative framework. A special attention in this article is drawn to legal support for the use of key technologies helping to provide security of aviation systems in future. The article demonstrates the ways to resolve legal challenges pertinent to ensuring air travel in the time of the COVID-19 crisis as well as within the post-crisis times. It suggests the ways to restore customers’ trust and to improve aviation security systems. COVID-19 as a threat, might keep affecting the world for many more years. In recent times, the technologies played a significant role in ensuring people’s and goods’ movement within a global scale, at the same time ensuring the safety of countries. But can these technologies play the same role in the times of the COVID-19 crisis? - «yes» Security technologies will increasingly pay an important role in diminishing the risks to safety and health of people. To play this role, the processes and technologies, the airports and air carriers shall restore the trust of travelers, through at the same time minimizing the need for quarantine measures around the globe. This will require further polishing and renewal of current approach, e.g. aviation security systems have to become smarter.